2016
DOI: 10.1016/j.atherosclerosis.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the vitamin D hypothesis: The NHANES III extended mortality follow-up

Abstract: The highest quartile compared to the lowest quartile of 25OH vitamin D levels is inversely associated with CHD and all-cause mortality adjusting for multiple confounders. Whether supplementation of individuals with low vitamin D will result in similar benefits will require a randomized clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 19 publications
4
20
0
Order By: Relevance
“…The data collected were used to study the prevalence of health behaviors and risk factors, including anthropometric parameters [27, 3235]. Subjects were interviewed and examined during 1988–1994.…”
Section: Methodsmentioning
confidence: 99%
“…The data collected were used to study the prevalence of health behaviors and risk factors, including anthropometric parameters [27, 3235]. Subjects were interviewed and examined during 1988–1994.…”
Section: Methodsmentioning
confidence: 99%
“…The low levels of vitamin D in these studies may be due to different confounding factors such as environment, age, sex, socioeconomic status, and nutritional status. Daraghmeh et al [24] conducted an NHANES III follow-up study on extended mortality and found that low vitamin D levels are inversely associated with CAD and all-cause mortality adjusting for multiple confounders. In animals, Assalin et al [25] studied the effect of vitamin D deficiency on cardiac metabolism, morphology, and function using male weanling Wistar rats.…”
Section: Introductionmentioning
confidence: 99%
“…lead, hydrocarbons, polychlorinated biphenyls) and blood nutrients (eg. carotenoids, Vitamin D, folate, and Vitamin E) that appear to substantially modify the prevalence of periodontitis in the population [146151] (Figure 3B). Moreover, dietary polyphenols in a wide range of foods have also been shown to function via anti-inflammatory and antioxidant mechanisms [152], thus having the potential to impact various mechanisms to reduce the initiation and progression of periodontitis.…”
Section: The Exposome and Nutritional Immunology Of Aging And Periodomentioning
confidence: 99%